Electron paramagnetic resonance spectroscopy for analysis of free radicals in zebrafish. - Mitra Sabetghadam Moghadam; Eli Wiens; Sébastien Gauvrit; Ramaswami Sammynaiken; Michelle M Collins (PLoS ONE)
Electron paramagnetic resonance (EPR) is an excellent choice for detecting free radicals in biological samples. Biologically relevant radicals are extremely short-lived and cannot be detected directly, emphasizing the need for an appropriate compound to generate stable adducts that can be measured by EPR. Spin trapping with nitrone compounds like 5,5-dimethyl-1-pyrroline N-oxide (DMPO) is a method commonly employed for detecting free radicals. However, due to the instability of nitrone radical adducts, using the cell-permeable 1-hydroxy-3-methoxycarbonyl-2,2,5,5-tetramethyl pyrrolidine (CMH) appears to be a more effective approach within biological tissues. Here, we compare the use of DMPO and CMH to detect the most abundant reactive oxygen species radical, superoxide ([Formula: see text]), in zebrafish and present an optimized protocol for performing EPR with a CMH spin probe in both zebrafish hearts and larvae. Together, our data suggest that EPR using the CMH probe is a reliable method to detect [Formula: see text] in zebrafish pathologies linked to oxidative stress, such as cardiovascular diseases.